Rapid Assembly of yeast expression cassettes for phenylpropanoid biosynthesis in Saccharomyces cerevisiae - Ahmad Bazli Ramzi; Ku Nurul Aqmar Ku Bahaudin; Syarul Nataqain Baharum; Muhammad Lutfi Che Me; Goh, Hoe-Han; Maizom Hassan; Normah Mohd Noor (Penerbit Universiti Kebangsaan Malaysia, 2018)
Microbial production of natural products using metabolic engineering and synthetic biology approaches often involves the assembly of multiple gene fragments including regulatory elements, especially when using eukaryotes as hosts. Traditional cloning strategy using restriction enzyme digestion and ligation are laborious and inflexible owing to the high number of sequential cloning steps, limited cutting sites and generation of undesired ‘scar’ sequences. In this study, a homology-based isothermal DNA assembly method was carried out for one-step simultaneous assembly of multiple DNA fragments to engineer plant phenylpropanoid biosynthesis in Saccharomyces cerevisiae. Rapid construction of yeast plasmid harboring dual gene expression cassettes was achieved via isothermal assembly of four DNA fragments designed with 20 bp overlapping sequences. The rate-limiting enzyme of phenylpropanoid pathway, cinnamate 4-hydroxylase encoded by C4H gene from Polygonum minus was cloned in tandem with yeast promoter and terminator elements of S. cerevisiae for efficient construction of phenylpropanoid biosynthetic pathway in recombinant yeast. The assembled pAG-CAT (C4H-ADH1t-TEF1p) shuttle plasmid and transformation of S. cerevisiae with the plant C4H gene were confirmed via PCR analysis. Based on these findings, the yeast shuttle plasmid harboring P. minus phenylpropanoid biosynthesis gene was efficiently constructed to be the starting platform for the production of plant natural products in genetically-engineered S. cerevisiae.